Navigating moral trade-offs - Kai Barron; Robert Stüber; Roel van Veldhuizen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
An extensive literature documents that people are willing to sacrifice personal material gain to adhere to a moral motive. However, less is known about the psychological mechanisms that operate when two moral motives come into conflict. We hypothesize that individuals adhere to the moral motive that aligns with their self-interest. We test this hypothesis using experiments that induce a conflict between two of the most-studied moral motives: fairness and truth-telling. Consistent with our hypothesis and across experiments, our results show that individuals do prefer to adhere to the moral motive that is more aligned with their self-interest.
Keywords: C91; D01; D63; D90; 330; Moral dilemmas; Dictator game; Lying game; Motives; Motivated reasoning